Cost structure and economies of scale in German water supply - Michael Zschille (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
Potable water supply in Germany is highly fragmented. A consolidation of the industry could, therefore, lead to lower cost of water supply and price savings for the customers. In this paper we estimate a total cost function for potable water supply based on a unique sample of German water utilities observed between 2004 and 2010. Newly available data allows for a detailed cost modeling approach. Capital stocks are estimated using the Perpetual Inventory Method, while capital costs are estimated using a weighted cost of capital approach. Local water suppliers are found to have strong cost advantages compared to regional suppliers. While the results indicate strong density effects, economies of scale are only found for the smallest water utilities. Thus, the results argue against a consolidation of the industry.
Keywords: C14; L22; L95; Q25; 330; water supply; cost function; economies of scale; seemingly unrelated regression